2018
DOI: 10.1002/cphc.201701264
|View full text |Cite
|
Sign up to set email alerts
|

Micropolarity and Hydrogen‐Bond Donor Ability of Environmentally Friendly Anionic Reverse Micelles Explored by UV/Vis Absorption of a Molecular Probe and FTIR Spectroscopy

Abstract: In the present work we show how two biocompatible solvents, methyl laurate (ML) and isopropyl myristate (IPM), can be used as a less toxic alternative to replace the nonpolar component in a sodium 1,4-bis-2-ethylhexylsulfosuccinate (AOT) reverse micelles (RMs) formulation. In this sense, the micropolarity and the hydrogen-bond ability of the interface were monitored through the use of the solvatochromism of a molecular probe (1-methyl-8-oxyquinolinium betaine, QB) and Fourier transform infrared spectroscopy (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This could be an alternative when a classical toxic solvent needs to be replaced by a non-toxic solvent for biological applications. More recently, the micropolarity and the hydrogen-bond ability of the interface of these RMs, ML/Na-AOT/water, and IPM/Na-AOT/water were monitored through the use of the solvatochromism of a molecular probe (1-methyl-8-oxyquinolinium betaine, QB) and Fourier transform infrared spectroscopy (FT-IR) [ 111 ]. The studies confirmed that due to the dissimilar penetration of these oils into the interfacial region, the micropolarity and the encapsulated water structure were different.…”
Section: Biocompatible Solvents As the External Phase In Rms And Microemulsions/nanoemulsionsmentioning
confidence: 99%
“…This could be an alternative when a classical toxic solvent needs to be replaced by a non-toxic solvent for biological applications. More recently, the micropolarity and the hydrogen-bond ability of the interface of these RMs, ML/Na-AOT/water, and IPM/Na-AOT/water were monitored through the use of the solvatochromism of a molecular probe (1-methyl-8-oxyquinolinium betaine, QB) and Fourier transform infrared spectroscopy (FT-IR) [ 111 ]. The studies confirmed that due to the dissimilar penetration of these oils into the interfacial region, the micropolarity and the encapsulated water structure were different.…”
Section: Biocompatible Solvents As the External Phase In Rms And Microemulsions/nanoemulsionsmentioning
confidence: 99%
“…In fact, it is difficult to investigate the properties of intermolecular H‐bonds clearly, such as proportion of free sites, H‐bonding length, and strength due to the limitations of traditional characterization such as FT‐IR, Raman spectrum, and NMR. [ 12 ] Molecular Dynamics (MD) simulation is proven an effective tool with a provision of atomic‐scale information and has become a powerful simulation technique. Numerous researchers have studied different polymers at multilevel scales by MD simulation, [ 13 ] including the behavior and properties of polymer chains at the molecular level, the aggregation structure at large scale, and the macroscopic physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the corresponding AOT RMs and some properties of these system such as W 0 , droplets size values, CMC, and N agg , among others, depending strongly on the chemical structure of the external solvent. 3,4,7 However, the search for new nonpolar and nontoxic solvents for the elaboration of more RMs still remains of interest. In this context, solvents derived from biomass, named as biobased solvents, could be a good alternative for this purpose.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reversed micelles (RMs) are organized systems of nanometric size formed by three components, i.e., a polar solvent (generally water), a surfactant, and some nonpolar solvent which form a thermodynamically stable and optically transparent solution . Due to the diverse applications of RMs, , in the past decade there has been much interest in assessing the nature of the surfactants and of nonpolar solvents that can be part of these organized systems. One of the surfactants more often used to form RMs is the anionic sodium 1,4-bis-2-ethylhexylsulfosuccinate (AOT, Scheme ). Diverse RMs using AOT and different organic nonpolar solvents, aromatic and aliphatic, have been reported .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation